Values Reflected in Pictorial Content of Textbooks at Elementary Level of Education in West Bengal, India - Ankur Nandi; Tarini Hader; Tapash Das (Journal of Elementary and Secondary School, 2024)
Textbooks function as catalysts for social change, influencing students’ values, beliefs, and cultural awareness from the primary education level. Textbooks serve as key learning resources for students that significantly influence students’ character development. Values should be incorporated into textbooks. Images in textbooks are powerful tools for shaping the values of students by engaging them visually, providing real-life context, fostering emotional connections, and promoting critical thinking and cultural sensitivity. The creation of textbooks that reflect current values is essential, and achieving this goal requires a comprehensive assessment of textbooks. This study investigates images used in primary education textbooks in West Bengal, India, to examine the representation of values. A total of 39 textbooks were analyzed, with eight key textbooks selected for in-depth analysis: ‘Amar Boi’ for classes I, II, and III, ‘Patabahar’ for classes IV and V, and ‘Atit O Aitihya’ for classes VI, VII, and VIII. These textbooks were chosen based on their widespread use and significance in the curriculum in govt. school in West Bengal. This study adopted qualitative and documentary research approaches through content analysis. The findings demonstrate that social, moral, environmental, spiritual, and historical values are emphasized across textbooks, reflecting the dominant cultural, social, or national values of the region. The findings of this study provide a foundation for policy changes at the state or national level to ensure the development and implementation of guidelines that promote value-balance content in educational materials and are useful for textbook development agencies, textbook writers, and teachers in developing value-alignment curricula and creating more inclusive, culturally sensitive, and ethically grounded visual materials.